A 3D modelling approach to measuring structural characteristics of bird nest interiors - Jing‐Chia Guo; Pei‐Jen Lee Shaner; Chih‐Ming Hung (Methods in Ecology and Evolution)
Abstract Nests are considered extended phenotypes of animals with potentially serious fitness consequences for the survival of offspring. Therefore, nest characteristics may contain valuable information about the underlying ecological and evolutionary mechanisms shaping animal reproduction. However, we currently lack efficient tools to archive nests and measure their characteristics, particularly concerning enclosed nests. Here we developed a step‐by‐step protocol of a 3D modelling approach to measure structural characteristics of nest interiors using the enclosed, dome‐shaped nests of Asian house martins as a test system. We first created the replicas of nest interiors using polyurethane (‘physical replicas’), from which 3D models were constructured using Metashape software (‘digital replicas’). We then estimated the volume and entrance area size of the digital replicas of nest interior using Metashape. To verify that the digital replicas preserve the structural characteristics of the physical replicas, we measured the volume and entrance area size of the physical replicas with Archimedes' drainage method and ImageJ, respectively. We then compared the manual measurements of the physical replicas to the values estimated from digital replicas. The estimates on the interior volume and entrance area size of 50 Asian house martin nests were nearly identical between physical and digital replicas. These results verified that the digital replicas are as reliable as the physical replicas for measuring structural characteristics of nest interior. Our 3D modelling approach allows for easy archiving as digital replicas of nest interiors endure preservation over time much better than actual nest specimens. Furthermore, digital replicas can be shared via internet and analysed for different aspects of morphometrics at any time by anyone. Overall, this tool should facilitate research on the ecology and evolution of animals in relation to nest construction.